2004
DOI: 10.1038/sj.bjp.0705650
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Concern: Carrageenan‐induced mouse paw oedema is biphasic, age‐weight dependent and displays differential nitric oxide cyclooxygenase‐2 expression

Abstract: Injection of carrageenan 1% (50 μl) in the mouse paw causes a biphasic response: an early inflammatory response that lasts 6 h and a second late response that peaks at 72 h, declining at 96 h. Only mice 7‐ or 8‐week old, weighing 32–34 g, displayed a consistent response in both phases. In 8‐week‐old mice, myeloperoxidase (MPO) levels are significantly elevated in the early phase at 6 h and reach their maximum at 24 h to decline to basal value at 48 h. Nitrate+nitrite (NOx) levels in the paw are maximal after 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
247
1
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(291 citation statements)
references
References 19 publications
(38 reference statements)
21
247
1
22
Order By: Relevance
“…Carrageenan induced paw edema in a biphasic phenomenon (Swingle, 1974). The initial phase involves the release of mediators such as histamine, serotonin and bradykin in while the late phase is characterized by infiltration of leukocytes and prostaglandins biosynthesis (Posadas et al, 2004). In this study, a significant edema reduction was observed at the first, the third and fifth hours.…”
Section: Discussionsupporting
confidence: 49%
“…Carrageenan induced paw edema in a biphasic phenomenon (Swingle, 1974). The initial phase involves the release of mediators such as histamine, serotonin and bradykin in while the late phase is characterized by infiltration of leukocytes and prostaglandins biosynthesis (Posadas et al, 2004). In this study, a significant edema reduction was observed at the first, the third and fifth hours.…”
Section: Discussionsupporting
confidence: 49%
“…20 Carrageenan-induced rat paw edema, a fully characterized model from past, is a routine test to determine the anti-inflammatory activity and its underling mechanisms. 21 Taking into account the former findings on superior anti-inflammatory and immunomodulatory of antioxidants and diterpenes, it was decided to research on anti-inflammatory activity of M. vulgare on carrageenan-induced paw edema in rats. So, herein, the effect of M. vulgare methanolic extract together with its antioxidant activity in different in vitro models was evaluated, with an approach to introduce a medicinal herb with antiinflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory mediators-histamine, serotonin, bradykinin, tachykinins, complement and ROS are responsible for inducing the inflammation (Morris, 2003). Prostaglandins then induce the last phase of the oedema; as a result of the action of inducible forms of nitric oxide synthase (iNOS) and cyclooxygenase (COX-2) (Posadas et al, 2004). Preemptive and curative administration of AZEto chicks significantly suppressed the acute local oedema in both treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…and diclofenac (3-30 mg/kg, i.p.) (Roach and Sufka, 2003). Figures 1(a, c) Analysis of the curves with respect to the vehicle control group shows a significant reduction in the mean maximal paw oedema at 2-3 h by AZE (prophylaxis: F 3,20 …”
Section: Carrageenan-induced Pedal Oedema Testmentioning
confidence: 97%
See 1 more Smart Citation